A Stakeholder Analysis of Visibility Versus Accountability in the Ethical Identity Disclosures of African Islamic Banks - Wajeeha Tayob; Riyad Moosa (International Journal of Islamic Business and Economics (IJIBEC), 2026)
This study examines the ethical identity disclosure practices of selected Islamic banks in Africa using the Ethical Identity Index (EII) framework. Based on content analysis of annual reports from four banks from 2021 to 2023, the study assesses the extent to which banks communicate key ethical dimensions, including zakah (alms giving), governance, products and services, and commitments to society and debtors. The findings reveal generally high disclosure in publicly visible areas such as debtor policies and vision and mission statements, but weaker disclosure in sharī‘ah governance, zakah, and top management transparency. These results suggest that banks prioritise external visibility over internal accountability, a pattern consistent with stakeholder theory. Compared to earlier studies from other regions, the African banks in this sample demonstrate more substantial alignment in some dimensions, which may reflect improved disclosure practices over time. The study contributes to the literature by applying the EII in an underexplored regional context and demonstrates how evolving African markets prioritise publicly visible commitments over internal governance to satisfy stakeholder expectations, thereby providing theoretical insights into how ethical identities are constructed in emerging Islamic finance sectors.